All we have done is interpret the sentiment of the Argentine people: Leopoldo F. Galtieri - Dagatti, Mariano Jesús (2015)
"In late 1982, hardly any other country in the world was in a more alarming and unfortunate situation". This statement by David Rock, in his book Argentina 1516-1987, although it does not lack the pathos of hyperbole, concisely describes the political, social and economic crisis in Argentina after seven years of military dictatorship. On 2 April, 1982, General Leopoldo Fortunato Galtieri, third de facto president of the self-styled "National Reorganisation Process", from the balcony of the Government House addresses a cheering crowd celebrating the momentary recovery of the Falkland Islands, after almost 150 years under British rule.